The Chemical Diversity of Lantana camara: Analyses of Essential Oil Samples from Cuba, Nepal, and Yemen. Issue 3 (March 2016) - Satyal, Prabodh; Crouch, Rebecca A.; Monzote, Lianet; Cos, Paul; Awadh Ali, Nasser A.; Alhaj, Mehdi A.; Setzer, William N.
Abstract : The aerial parts of Lantana camara L. were collected from three different geographical locations: Artemisa (Cuba), Biratnagar (Nepal), and Sana'a (Yemen). The essential oils were obtained by hydrodistillation and analyzed by gas chromatography/mass spectrometry. A cluster analysis of 39 L. camara essential oil compositions revealed eight major chemotypes: β ‐caryophyllene, germacrene D, ar ‐curcumene/zingiberene, γ ‐curcumen‐15‐al/ epi ‐ β ‐bisabolol, ( E )‐nerolidol, davanone, eugenol/alloaromadendrene, and carvone. The sample from Cuba falls into the group dominated by ( E )‐nerolidol, the sample from Nepal is a davanone chemotype, and the sample from Yemen belongs to the β ‐caryophyllene chemotype. The chemical composition of L. camara oil plays a role in the biological activity; the β ‐caryophyllene and ( E )‐nerolidol chemotypes showed antimicrobial and cytotoxic activities.